An Augmented Reality application for training upper limb amputees - Lima, Diogo Aparecido Cavalcante de; Lamounier Júnior, Edgard Afonso; Cardoso, Alexandre; Soares, Alcimar Barbosa; Cavalcante, Reidner Santos; Mattioli, Leandro Resende; Cyrino, Gabriel Fernandes; Silva, Alexandre Carvalho (Anais do Simpósio de Realidade Virtual e Aumentada (SVR); 2022: Anais do XXIV Simpósio de Realidade Virtual e Aumentada, 2022)
Amputation is a traumatic process where the person needs to start rehabilitation immediately to regain physical independence. Traditionally, rehabilitation periods take up to 12 months and have abandonment rates above 35%. Initiatives to train amputees through Augmented Reality (AR) can provide more realistic and engaging experiences. This paper presents an AR application for upper limb amputee rehabilitation, using a Vuzix®1200 HMD as the output interface. Tracking of the amputee stump happens in real-time through markers. For opening and closing the virtual prosthesis hand, the application communicates with an auxiliary device through Bluetooth. The application is a serious game based on traditional rehabilitation exercises. The system was tested by seven volunteers without amputation and despite the need for larger studies for clinical evaluation, the results of the application's functioning are encouraging.